Analisis Penerapan Pemungutan PPN pada PT PLN Indonesia Power UBP Suralaya - Niken Ardiana Listy; Mulyanah Mulyanah; Intan Puspanita; Selly Anggraeni Haryono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Collecting taxes is the main sources for countries to generate revenues to finance goverment expenditure and investments in human capital, infrastructure, and the provision of services for the society. Value added taxes (VAT) as one of collecting taxes process to generate the government’s revenue. The aim of this study is to find out the implementation of VAT collection at PT PLN Indonesia Power UBP Suralaya as State-Owned Enterprises is a mandatory VAT collector according to Minister of Finance Decree Number.30/KMK.03/2021 with last amended by Minister of Finance Decree Number.240/KMK.03/2022 and also to find out the obstacles during the implementation of VAT collection at PT PLN Indonesia Power UBP Suralaya. The method used in this study is a descriptive method. Data collection methods by using interview methods, literature study methods, and documentation methods. The results of this study finds that the PT PLN Indonesia Power UBP Suralaya has carried out the collection and deposit of VAT procedure. However, there were obstacles when preparing and uploading tax invoices in which the failures or rejections occurred due to internet network disruptions